Potensi Sektor Pertanian dalam Pembangunan Ekonomi di Kabupaten Jembrana - YUNDARI, NI KOMANG WIDYA; SUDARMA, I MADE; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022DO - 10.24843/JAA.2022.v11.i01.p42, 2022)
The Potential of the Agricultural Sector in the Economic Development of Jembrana Regency.  The agricultural sector in Jembrana Regency is the sector that provides the largest contribution to the regional domestic product of the Province of Bali, amounting to Rp 1,810,266.32 million. Based on the available resources, Jembrana Regency has an agricultural land area of 38.5% and most of the population work as farmers (28.01%). However, the agricultural sector has not been able to become a driving force to develop the potential of the agricultural sector in Jembrana Regency to the fullest. This study aims to analyze: (1) the position of Jembrana Regency in the regional economy in Bali Province, (2) the position of the agricultural sector in the regional economy in Jembrana Regency and (3) the types of agricultural commodities which are the leading commodities in Jembrana Regency. The results show that the position of Jembrana Regency in the regional economy in Bali Province is within quadrant IV, meaning that it is a relatively underdeveloped area. The position of the agricultural sector in Jembrana Regency is within quadrant I, meaning that the sector is progressing and growing rapidly. The results of the Location Quotient analysis show that the leading commodities in Jembrana Regency for the food crop sub sector are rice, soybeans and green beans, while in the horticultural crop sub sector are long beans, large chilies, cucumbers, eggplants, watermelons, melons, bananas, rambutan, pineapple, duku and soursop. This research is expected to help the local government in determining priorities and policies in developing the agricultural sector in the Jembrana Regency so that it could transform Jembrana Regency into a developed and growing region.